Relationship Between Nurses\' Spiritual Care Competence and Family Satisfaction in Critical Care Units - Fatemeh Mohebbi; Masoumeh Heidari; Reza Norouzadeh (Health, Spirituality and Medical Ethics)
Background and Objectives: Spiritual competence can help patients recover and achieve better health outcomes. This study examines the relationship between nurses’ spiritual care competence and family satisfaction of patients admitted to critical care units (CCUs). Methods: This was a cross-sectional study conducted from July to December 2023. A total of 123 adult critical care nurses and 123 family members of patients were randomly selected from social security hospitals in Tehran City, Iran. Data collection tools included the spiritual care competence scale, nurses’ spiritual care competency questionnaire, and family satisfaction in the intensive care unit (ICU) questionnaire. The SPSS software, version 24, was used for data analysis. Results: The results showed the high competence of spiritual care in critical care nurses (104.60±18.47). The nurses’ lowest score of spiritual care competence was in the assessment and implementation (17.90±6.45 out of 30), and the best score was in communication (9.23±1.07 out of 10). The results showed that families had the lowest level of satisfaction in decision-making (48.62±21.23 out of 100), and the highest score was in satisfaction with care (51.60±19.54 out of 100). The findings indicated that the competence of nurses in spiritual care is not correlated to family satisfaction. Conclusion: The weak correlation between nurses’ spiritual care competence and family satisfaction highlights the complexity of factors influencing spiritual well-being in healthcare. The authors suggest further research into the factors affecting nurses’ spiritual care competence and the impact of related training on nursing practice quality.